THE ROLE OF HOUSEWIVES IN COMBATING COVID-19 THROUGH KNOWLEDGE - Apriyani, Desi; Wesnina, Wesnina; Lubis, Harsuyanti Rawiyah (Prosiding Pendidikan Teknik Boga Busana, 2023)
This research aims to get an information of the knowledge of housewives on masks. This study uses quantitative research methods with a descriptive approach. The number of respondents is 108 respondents who live in Batu Ampar (Condet) Sub District in East Jakarta. Primary data in this study was obtained by distributing questionnaires. The level of knowledge of masks is divided into 5 aspects, namely based on Remembering (C1), Understanding (C2), Applying (C3), Analyzing (C4), and Evaluating (C5). Research results obtained (C1) 59.26%, (C2) 77.04%, (C3) 65.90%, (C4) 85.80%, (C5) 85.19% of respondents can validate the use of masks. From the calculation results on the knowledge indicator, it was found that the frequency of the correct answer was 81 correct answers or 75%, then the knowledge of housewives on masks could be categorized as quite good at knowing about masks. Keywords: housewife, knowledge, mask